2018
DOI: 10.1590/1678-7757-2017-0231
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular calcium increases fibroblast growth factor 2 gene expression via extracellular signal-regulated kinase 1/2 and protein kinase A signaling in mouse dental papilla cells

Abstract: We previously reported that elevated extracellular calcium (Ca2+) levels increase bone morphogenetic protein 2 expression in human dental pulp (hDP) cells. However, it is unknown whether extracellular Ca2+ affects the expression of other growth factors such as fibroblast growth factor 2 (FGF2).Objective:The present study aimed to examine the effect of extracellular Ca2+ on FGF2 gene expression in hDP and immortalized mouse dental papilla (mDP) cells.Materials and Methods:Cells were stimulated with 10 mM CaCl2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…CB2R agonists inhibit cAMP production which has been demonstrated to result in phosphorylation of ERK in the in vitro models 109,111,120‐123 . On the contrary, inverse agonists increase cAMP levels that could activate protein kinase A (PKA) and subsequent phosphorylation of ERK can occur as such is reported in dental pulpal cells 124 and pancreatic β cells 125,126 . The increase in p‐ERK may exert anti‐inflammatory activity via suppression of NF‐κB activation as reported in vascular endothelial cells 127 .…”
Section: Discussionmentioning
confidence: 98%
“…CB2R agonists inhibit cAMP production which has been demonstrated to result in phosphorylation of ERK in the in vitro models 109,111,120‐123 . On the contrary, inverse agonists increase cAMP levels that could activate protein kinase A (PKA) and subsequent phosphorylation of ERK can occur as such is reported in dental pulpal cells 124 and pancreatic β cells 125,126 . The increase in p‐ERK may exert anti‐inflammatory activity via suppression of NF‐κB activation as reported in vascular endothelial cells 127 .…”
Section: Discussionmentioning
confidence: 98%
“…demonstrated that cAMP/PKA and Ras/ERK pathways were linked together and regulated the expressions and phosphorylation of ERK1/2 in melanoma cells . Research on dental papilla cells revealed ERK1/2 and PKA signaling were involved in the regulation of fibroblast growth factor‐2 by extracellular calcium . However, the relationship between PKA and ERK1/2 in cementogenesis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This bioactive effect has been related to extracellular signal -regulated kinase 2 (ERK1/2) and Mad- related protein 1 (Smad1) pathways, in a mechanism independent of mevalonate, ultimately with bone morphogenetic protein 2 (BMP-2) overexpression, which seems to result in autocrine and paracrine stimulation (Ghosh-Choudhury et al 2007; Chen et al 2010; Karanxha et al 2013; Soares, Anovazzi, et al 2018; Soares, Zhang, et al 2018). The influx of Ca 2+ into cells activated unspecified Ca 2+ channels, which, in turn, led to ERK1/2 phosphorylation along with DSPP, ALP, fibroblast growth factor 2, osteopontin (OPN) and osteocalcin (OCN) overexpression (Woo et al 2013; Li et al 2015; Kanaya et al 2018; Kulan et al 2018). In addition, Smad 1/5/8-BMP-2 activation has also been closely related to the osteogenic differentiation of precursor cells in contact with calcium-releasing sources (Li et al 2015; Kanaya et al 2018).…”
Section: Discussionmentioning
confidence: 99%